Cantrang and Poverty Fisherman in Tegal, Central Java - -, Rohayati -; Kinseng, Rilus A (Sodality: Jurnal Sosiologi Pedesaan, 2018)
The sea territorial of Tegal City are known to have abundant fishery resources, but fisherman poverty still occurs. The low welfare of fisherman is suspected due to the competition of catching areas and the use of trap fishing tools of cantrang type (seine nets) that can cause poverty of fishermen in Tegal City coastal. In addition, cantrang fishing tools alsi damage other fishing gear such as jarng, pancing, and arad. This study aims to analyze the poverty of fishermen community and known the influence of firsherman cantrang to poverty of fishermen in Tegal City. The research method used is survey method. Poverty analysis of fishermen using poverty line approach through 14 indicators of household poverty, and to known the influence of fisherman cantrang to poverty of fisherman using descriptive analysis approach. The result of the research by using the measurement of poverty line, shows that which include in the group of poor fisherman is fishing rod fisherman. However, based on the measurement of 14 indicantors of poor households, small fishermen who live in Tegal City coastal categorized as less prosperous family. The results also show that the existence of cantrang fisherman not affect the poverty of fishermen because of different fishing areas, cantrang fisherman fishing in  Sumatra and Kalimantan sea while small fishermen do catching around the sea of Tegal City.